Characterizing Non-Tuberculous Mycobacteria Infection in Bronchiectasis - Faverio, Paola; Stainer, Anna; Bonaiti, Giulia; Zucchetti, Stefano; Simonetta, Edoardo; Lapadula, Giuseppe; Marruchella, Almerico; Gori, Andrea; Blasi, Francesco; Codecasa, Luigi; Pesci, Alberto; Chalmers, James; et al. (International journal of molecular sciences, 2016)
Chronic airway infection is a key aspect of the pathogenesis of bronchiectasis. A growing interest has been raised on non-tuberculous mycobacteria (NTM) infection. We aimed at describing the clinical characteristics, diagnostic process, therapeutic options and outcomes of bronchiectasis patients with pulmonary NTM (pNTM) disease. This was a prospective, observational study enrolling 261 adult bronchiectasis patients during the stable state at the San Gerardo Hospital, Monza, Italy, from 2012 to 2015. Three groups were identified: pNTM disease; chronic P. aeruginosa infection; chronic infection due to bacteria other than P. aeruginosa. NTM were isolated in 32 (12%) patients, and among them, a diagnosis of pNTM disease was reached in 23 cases. When compared to chronic P. aeruginosa infection, patients with pNTM were more likely to have cylindrical bronchiectasis and a “tree-in-bud” pattern, a history of weight loss, a lower disease severity and a lower number of pulmonary exacerbations. Among pNTM patients who started treatment, 68% showed a radiological improvement, and 37% achieved culture conversion without recurrence, while 21% showed NTM isolation recurrence. NTM isolation seems to be a frequent event in bronchiectasis patients, and few parameters might help to suspect NTM infection. Treatment indications and monitoring still remain an important area for future research.